Validating parents' self-reports of children's exposure to potentially toxic substances within the home. Issue 3 (3rd June 2008) - Patel, B; Devalia, B; Kendrick, D; Groom, L
Abstract : Objective: To validate self-reported possession and storage of a range of substances within the home. Participants: 30 families with children aged 12–35 months on health visitor caseloads in Nottingham, UK. Methods: Self-reported possession and storage of potentially hazardous substances were validated by observations. Sensitivity, specificity, and predictive values were calculated for possession, storage, and exposure to substances. Results: Self-reported low exposure to substances had high sensitivities (87–100%) and positive predictive values (75–100%) for all substances, except toilet cleaner (positive predictive value 62%) and high negative predictive values for commonly owned household products. Specificity and negative predictive value could not be estimated reliably for medicines and less commonly owned household products, as few families stored these unsafely. Conclusions: A measurement of exposure that combines self-reported possession and storage may be sufficiently accurate to identify families with safer poison prevention practices.